2022
DOI: 10.3389/fcvm.2022.1049414
|View full text |Cite
|
Sign up to set email alerts
|

Empirical superior vena cava isolation improves outcomes of radiofrequency re-ablation in pulmonary vein isolation non-responders: A 2-center retrospective study in China

Abstract: BackgroundPulmonary vein isolation (PVI) is the standard ablation strategy for treating atrial fibrillation (AF). However, the optimal strategy of a repeat procedure for PVI non-responders remains unclear.ObjectiveThis study aims to investigate the incidence of PVI non-responders in patients undergoing a repeat procedure, as well as the predictors for the recurrence of repeat ablation.MethodsA total of 276 consecutive patients who underwent repeat ablation from August 2016 to July 2019 in two centers were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Gu et al have examined data from patients that have had AF recurrence and no PV reconnection during redo ablation, and found that empiric SVCI was associated with increased arrhythmia free survival (79.3 vs. 50.0%; HR: 0.338; 95% CI: 0.131–0.873; p = 0.025). This was a small retrospective study and larger randomized trials are much anticipated [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu et al have examined data from patients that have had AF recurrence and no PV reconnection during redo ablation, and found that empiric SVCI was associated with increased arrhythmia free survival (79.3 vs. 50.0%; HR: 0.338; 95% CI: 0.131–0.873; p = 0.025). This was a small retrospective study and larger randomized trials are much anticipated [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many patients with SVC foci are only discovered during redo ablation; hence, finding which clinical phenotype is benefited remains to be answered. ’’The increasing implementation of CBA and contact force RFA might lead to an era of reduced PV reconnection and the number of the so-called PVI non responders necessitating specialized treatment during redo ablation will increase [ 55 ]. Besides PVI non-responders, patients undergoing repeated CBA procedures [ 54 ] and patients with long SVC sleeves [ 26 , 41 ] or arrhythmogenic RSPV [ 22 , 34 ] could be optimal candidates for SVCI, especially via an empiric approach.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…For patients with persistent forms of AF, it is more likely to have non-PV triggers, such as the left atrial posterior free wall [ 18 , 19 , 20 ], the left atrial appendage [ 21 ], the superior vena cava (young patients with AF had a higher incidence of only non-PV foci, mostly located here) [ 22 , 23 , 24 , 25 ], the coronary sinus [ 26 , 27 ], and the ligament of Marshall [ 28 , 29 ]. For non-PV foci patients, the isolation of them was a significant factor affecting the achievement of better clinical outcomes following AF ablation [ 30 ].…”
Section: Pathophysiology Of Atrial Fibrillationmentioning
confidence: 99%